An analytical study (of the applied force and distance) at the moment of takeoff some hurdles and their effect on the achievement of the 100m hurdles run for female players - Ali Sadiq Dhiab; Zina Arkan Hameed; Ahmed Ali Sadeq (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective. Identify the reality of both (the force applied by the feet and the distance) at the moment of takeoff of some hurdles in the effective 100m hurdles for female players, and identify the reality of the achievement in the effective 100m hurdles among female players who have advanced to some Iraqi clubs.